Electric Current Effect on the Energy Barrier of Magnetic DomainWall Depinning: Origin of the Quadratic Contribution - Kim, Kab-Jin; Ryu, Jisu; Gim, Gi-Hong; Lee, Jae-Chul; Shin, Kyung-Ho; Lee, Hyun-Woo; Choe, Sug-Bong (AMER PHYSICAL SOC, 2011)
The energy barrier of a magnetic domain wall trapped at a defect is measured experimentally. When the domain wall is pushed by an electric current and/or a magnetic field, the depinning time from the barrier exhibits perfect exponential distribution, indicating that a single energy barrier governs the depinning. The electric current is found to generate linear and quadratic contributions to the energy barrier, which are attributed to the nonadiabatic and adiabatic spin-transfer torques, respectively. The adiabatic spin-transfer torque reduces the energy barrier and, consequently, causes depinning at lower current densities, promising a way toward low-power current-controlled magnetic applications.
Keywords: WALL; VISCOSITY; REVERSAL